Sustainable and diverse Islamic art: a social and cultural experiment in Australia / Abdul Attamimi and Majdi Faleh - Abdul Attamimi; Majdi Faleh (2015)
The legacy of Art in Islam is seen as an integral component of a whole civilization that extended from the far East to the far West. The Art of Islam largely contributed to both the spiritual and the material life of the artists and that of the citizens in the Islamic world. The intricate and complex Art of Islam, or what is called as Arabesque, is a representation of the apogee of a civilization that was once prosperous and creative. These same symbols also have a spiritual connotation as they symbolize the infinite creation of the universe. Added together, these initially simple, geometric patterns can be produced continuously to illustrate an unlimited image of the universe. Today, art continues to be produced freely in a global world dominated by universal values of environmental protection that Islam, among other schools of thought, came to promote. In the Quran, for instance, it is clearly stated that the excess of waste is not loved by Allah, and that each component of our environment is there for a specific reason. This paper discusses a cultural and social experiment that was started by Muslim students of the University of Western Australia (UWA). The inspiration is about creating Islamic art patterns and sculptures out of recyclable materials. This initiative revisits Islamic art in a contemporary one that transcends the classical ways of constructing art and engages with human values of environmental protection. Here our approach is to define how art can be historically reshaped engaging in a sustainable dialogue with religious values and cultural education.